(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This paper giving review of diverse aspects of scheduled castes in India. A brief overview of the caste system and discusses the types of groups and their social, economic, political, educational and cultural aspects too. This paper try to show the variation between developments of various group of scheduled castes. Through this paper we can say that there is region wise and caste wise variation in the process of development. Religion conversion from Hindu to other is also important factor in the process of development of scheduled castes